Surveillance of Parapoxvirus Among Ruminants in Virginia and Connecticut. (8th February 2013) - Roess, A. A.; McCollum, A. M.; Gruszynski, K.; Zhao, H.; Davidson, W.; Lafon, N.; Engelmeyer, T.; Moyer, B.; Godfrey, C.; Kilpatrick, H.; Labonte, A.; Murphy, J.; et al.
Summary In 2008, two deer hunters in Virginia and Connecticut were infected with a unique strain of pseudocowpox virus, a parapoxvirus. To estimate the prevalence of this virus, and in an attempt to define the reservoir, Parapoxvirus surveillance was undertaken between November 2009 and January 2010. 125 samples from four ruminant species (cows, goat, sheep and white‐tailed deer) were collected in Virginia, and nine samples from white‐tailed deer were collected in Connecticut. We found no evidence that the parapoxvirus species that infected the deer hunters is circulating among domesticated ruminants or white‐tailed deer. However, parapoxvirus DNA of a different parapoxvirus species, bovine papular stomatitis virus (BPSV), was detected in 31 samples obtained from asymptomatic cattle in Virginia. Parapoxvirus DNA–positive cattle originated from the same counties indicating probable transmission among animals. Molecular analysis identified BPSV as the parapoxvirus affecting animals. Asymptomatic parapoxvirus infections in livestock, particularly young animals, may be common, and further investigation will inform our knowledge of virus transmission.